Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

x (27-x) = 182
Please help me by solving this!​


Sagot :

We are provided with a expression as follows ;

  • [tex]{\sf x(27-x)=182}[/tex]

Can be further written as ;

[tex]{: \implies \quad \sf 27x-{x^{2}}=182}[/tex]

[tex]{: \implies \quad \sf {x^2} -27x + 182=0}[/tex]

Using splitting the middle term we have ;

[tex]{: \implies \quad \sf {x^2} - 13x-14x+182=0}[/tex]

[tex]{: \implies \quad \sf x(x-13)-14(x-13)=0}[/tex]

[tex]{: \implies \quad \sf (x-13)(x-14)=0}[/tex]

Case I :-

When , (x-13)=0 , then clearly x = 13

Case II :-

When , (x-14)=0 , then clearly x = 14

Hence , The required values of x are 13 and 14 respectively